2000
DOI: 10.1177/0146167200268005
|View full text |Cite
|
Sign up to set email alerts
|

Do You have to Pay Attention to Your Feelings to be Influenced by Them?

Abstract: Two experiments investigated how individual differences in attention to emotion influence the role of affect in judgments of risk. In Experiment 1, mood influenced the judgments of individuals high, but not low, in attention to emotion. When an attribution manipulation made a cause of their feelings salient, individuals high in emotional attention no longer perceived their feelings as relevant and were not influenced by them; whereas those low in emotional attention now paid attention to them and were influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
113
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 16 publications
8
113
2
Order By: Relevance
“…In contrast to our dysphoric sample, studies by Gasper and Clore (1998) have revealed that people with high trait anxiety do not reduce the impact of their current mood when making risk estimates, even if alternative sources for their current feelings are provided. Instead, they rely on their trait-consistent anxious affect that is perceived as relevant for the judgments to be made (see also Gasper and Clore 2000). Given these differences, the specific nature of our cue manipulation deserves further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our dysphoric sample, studies by Gasper and Clore (1998) have revealed that people with high trait anxiety do not reduce the impact of their current mood when making risk estimates, even if alternative sources for their current feelings are provided. Instead, they rely on their trait-consistent anxious affect that is perceived as relevant for the judgments to be made (see also Gasper and Clore 2000). Given these differences, the specific nature of our cue manipulation deserves further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…There is broad consensus that emotions directly affect judgment, decision making, and information processing (Clore, Gasper, & Garvin, 2001;Gasper & Clore, 2000;Kahneman & Ritov, 1994;Lowenstein, Weber, Hsee, & Welch, 2001). Thus, it should come as no surprise that theorists have long posited a relation between emotions and delusional and peculiar beliefs (e.g., Kraepelin, 1899Kraepelin, /1989.…”
Section: Introductionmentioning
confidence: 99%
“…Men in the low EA condition reported significantly higher levels of suspiciousness and lower levels of EA than men in the high EA condition. Women in both conditions reported equally high levels of EA, which were greater than those of men in both conditions, and the manipulation did not affect their levels of suspiciousness.There is broad consensus that emotions directly affect judgment, decision making, and information processing (Clore, Gasper, & Garvin, 2001;Gasper & Clore, 2000;Kahneman & Ritov, 1994;Lowenstein, Weber, Hsee, & Welch, 2001). Thus, it should come as no surprise that theorists have long posited a relation between emotions and delusional and peculiar beliefs (e.g., Kraepelin, 1899Kraepelin, /1989.…”
mentioning
confidence: 99%
“…For example, we included a manipulation check in all four experiments right after viewing the video. Attribution of the incidentally aroused emotion to the video may have dampened elevation's effect on attitudes toward gay men (Gasper & Clore, 2000;Schwarz & Clore, 2003). It is possible that removing the manipulation check after the video will magnify these effects.…”
mentioning
confidence: 99%